Quality of Health Services as a Determinant of Patient Satisfaction in Specialist Outpatient Clinics - Azmi, Rofiqah; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Patient satisfaction at specialist clinics is an important indicator in ensuring the quality of healthcare services. The level of patient satisfaction also determines the competitiveness and sustainability of healthcare institutions. The purpose of this study was to analyze the influence of healthcare service quality on patient satisfaction at specialist clinics. This study was conducted using a cross-sectional design, involving 177 outpatients selected using purposive sampling. Data were collected through questionnaires, then analyzed descriptively, using the Chi-Square test, and finally using multiple logistic regression. The results showed that variables that significantly influenced patient satisfaction were dignity (p = 0.040), confidentiality (p = 0.034), communication (p = 0.026), autonomy (p = 0.029), prompt attention (p = 0.005), quality of basic facilities (p = 0.001), and access to social support (p = 0.011). Meanwhile, choice of service provider did not show a significant influence (p = 0.208). Of all these variables, the quality of basic facilities had the greatest influence on patient satisfaction (odds ratio = 3.406). Furthermore, it was concluded that the quality of healthcare services is a determinant of patient satisfaction in specialist clinics. Management is expected to improve the quality of communication and education between healthcare workers and patients through training, educational media, and an empathetic approach to enhance patient satisfaction.Keywords: quality of healthcare services; patient satisfaction; specialist clinics